1968
DOI: 10.1111/j.1399-6576.1968.tb00734.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Acute Coronary Death

Abstract: SUMMARY In order to examine whether functional disturbances in the heart without significant lesions is a frequent cause of sudden cardiac death, two prospective autopsy studies were performed. In a series of 78 cases of myocardial ischaemia dying within 48 hours acute lesions in the major coronary arteries were found in 89 per cent in patients who had been on anticoagulant therapy at the onset of the acute disease and in 76 per cent of the untreated patients. The relative frequency of cases without acute coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The coronary arterial circulation in patients dying of myocardial ischemia was studied at autopsy by Jørgensen et al . [14,15], who found a few platelet aggregates downstream of coronary thrombi in 36% of 39 patients. In cases without upstream thrombi, the frequency of platelet aggregates in myocardial arteries was the same in cases of sudden death with rupture of, or hemorrhage into atherosclerotic plaques without complicating thrombi.…”
Section: Introductionmentioning
confidence: 99%
“…The coronary arterial circulation in patients dying of myocardial ischemia was studied at autopsy by Jørgensen et al . [14,15], who found a few platelet aggregates downstream of coronary thrombi in 36% of 39 patients. In cases without upstream thrombi, the frequency of platelet aggregates in myocardial arteries was the same in cases of sudden death with rupture of, or hemorrhage into atherosclerotic plaques without complicating thrombi.…”
Section: Introductionmentioning
confidence: 99%
“…Jergensen et al (29,30) in their autopsy study of patients dying suddenly of myocardial infarction found arterial platelet aggregates in the epicardial and myocardial arteries. In histologic studies of human hearts (31,32) platelet aggregates in cardiac vessels of suddenly deceased patients were found.…”
Section: Prostacyclin On Coronary Thrombosis In the Sudden-death Modelmentioning
confidence: 96%
“…Many authors attempted to graduate the histological findings of DVT, classifying the chronological phenomena into phases using histochemical methods only. The first attempt to subdivide the morphological The only pathological findings of the intramural arterial system reported in the literature associated with sudden death are platelet aggregates and fibrin-platelet thrombi or emboli (Jorgensen et al 1968;Haerem 1972;Frink et al 1978;El-Maraghi and Genton 1980;Falk 1985;Davies et al 1986). These lesions were considered responsible for acute ischaemia causing sudden death.…”
Section: Other Cardiac Conditionsmentioning
confidence: 99%